Pleiades or Not? Resolving the Status of the Lithium-rich M Dwarfs HHJ 339 and HHJ 430 - Stauffer, J; Barrado, D; David, T; Rebull, LM; Hillenbrand, LA; Mamajek, EE; Oppenheimer, R; Aigrain, S; Bouy, H; Lillo-Box, J (American Astronomical Society, 2020)
Oppenheimer et al. discovered two M5 dwarfs in the Pleiades with nearly primordial lithium. These stars are not low enough in mass to represent the leading edge of the lithium depletion boundary at Pleiades age (~125 Myr). A possible explanation for the enhanced lithium in these stars is that they are actually not members of the Pleiades but instead are members of a younger moving group seen in projection toward the Pleiades. We have used data from Gaia DR2 to confirm that these two stars, HHJ 339 and HHJ 430, are indeed not members of the Pleiades. Based on their space motions, parallaxes, and positions in a Gaia-based color–magnitude diagram, it is probable that these two stars are about 40 parsecs foreground to the Pleiades and have ages of ~25 Myr. Kinematically they are best matched to the 32 Ori moving group.